(Why) did Desertec fail? An interim analysis of a large-scale renewable energy infrastructure project from a Social Studies of Technology perspective. Issue 7 (3rd July 2018) - Schmitt, Thomas M.
ABSTRACT: In 2009 the Desertec Industrial Initiative (DII) was founded by several, predominant German enterprises. The objective of DII was to organise the conditions for the realisation of the Desertec idea, which aimed to both (a) supply Europe, in a large-scale manner, with electricity produced in solar power plants in North Africa and the Arabic peninsula and (b) contribute to the self-supply of the Middle East North Africa region (MENA). Protagonists of the desert energy idea saw this megatechnic project as a starting point for a new trans-Mediterranean EU-MENA union, critics in contrast as a neo-colonial project. Disputes over the adequate interpretation and implementation of the Desertec idea broke out from the beginning. In 2014/2015, the media talked of the failure of DII and of the Desertec concept. The majority of the members left DII at the end of 2014. On the other hand, in some MENA countries renewables are playing a crucial role in securing the future of the energy sector. This paper analyses the development of DII and the Desertec idea by using concepts from Social Studies in Technology, and especially by the multi-level perspective approach in Transition Studies. It shows how the interplay of different factors, such as technological developments, entrepreneurial performances and political processes, lead to internal conflicts and the non-realisation – up to now – of related large-scale energy projects. As an important aspect of the paper, different understandings of the future of our energy supply and of North–South relations are presented in detail.